FACTORS AND STRATEGIES TO DEVELOP CRITICAL THINKING IN ACADEMIC WRITING: A CASE OF EFL STUDENTS AT ONE UNIVERSITY IN JAMBI - Fajaryani, Nunung; Abrar, Mukhlash; Yeni, Fitra (Universitas Jambi, 2024)
At the university level, critical thinking is an essential yet challenging skill for EFL students. EFL students often face various barriers to developing this skill. The purpose of this study is to explore the factors that influence EFL students' abilities and to investigate the strategies they employ to develop critical thinking skills in academic writing. This study used a qualitative research design with a case study approach while the data was collected through semi-structured interviews with ten participants, specifically eighth-semester students majoring in English at a public University in Jambi. The researcher used purposive sampling to select participants based on specific criteria. The researcher used thematic analysis as a method to examine and interpret the collected data. The findings show that EFL students face several factors that affect their ability to develop critical thinking in academic writing including personal competence factors (lack of topical knowledge), linguistic factors (grammar and vocabulary), and psychological factors (low motivation, lack of self-confidence, and anxiety in supervision),. However, despite these influencing factors, EFL students also apply strategies to overcome challenges when developing critical thinking in academic writing, specifically self-management, technology support, learning atmosphere, support system, and mentorship schedule management. It can be concluded that this research is expected to be useful as suggestions and recommendations aimed to develop critical thinking in academic writing, especially for Indonesian students at the undergraduate level.